Simulasi Kesiapsiagaan Masyarakat dalam Memberikan Pertolongan Korban Bencana Kebakaran dengan Model Triase Pre Hospital - Suryadi; Aguspairi (Jurnal Pengabdian Masyarakat, 2025)
Jambi is one of the provinces in Indonesia that is prone to fire disasters, especially during the dry season, such as forest fires or house fires, causing significant losses for the people affected by the disaster. The problems that arise in the community are not knowing how to help fire victims so that they can be saved and not disabled by using the Pre-Hospital Disaster Triage model, from a survey conducted through interviews with 10 people about initial disaster management in their environment if a fire occurs, not knowing how to provide assistance to victims of the disaster and confused about what to do to save the lives of victims. Based on this phenomenon, it is necessary to carry out education and simulation of community preparedness with the pre-hospital triage model.